Model for Determining the Stability of Retail Deposits with Higher Outflow Rates - Murks Bašič, Aleksandra (Naše gospodarstvo/Our economy, 2015)
Retail deposits are treated as one of the cheapest and most stable funding sources for banks, especially for those with high volumes of retail deposits. A bank defines three main categories of retail deposits that are subject to different outflow rates for the purpose of liquidity coverage requirements in reporting and compliance. The outflow rates for the first two main groups are 5% and 10% respectively, but for the third main group the bank calculates its own outflow rates. We analyzed the latter in this paper. Each bank should assign retail deposits to one of the three categories based on the number and type of predetermined risk factors. Risk factors are divided into two groups according to the degree of risk. The paper first describes the legislative framework, followed by the method of calculating higher outflow rates for retail deposits according to the historical movements and the expected volatility assessment in the situation of stress conditions. At the end of the paper, we briefly provide the future treatment of retail deposits with higher outflow rates.